Novel Insight into the Mechanism of Metabolic Surgery Causing the Diversity in Glycemic Status in Type 2 Diabetes - Zhou, Mengxiao; Wang, Lijuan; Zhou, Lujin; Chang, Xiaotong; Zhu, Xiaobo (Experimental and Clinical Endocrinology & Diabetes, 2022)
Metabolic surgery results in diverse glycemic status in patients with type 2 diabetes (T2D), including hyperglycemia without remission, significant amelioration of hyperglycemia with partial remission, complete restoration of euglycemia, or with prolonged remission, hyperglycemia recurrence in relapses after remission, or post-bariatric hypoglycemia. Unfortunately, it is not known how metabolic surgery leads to this diverse consequence. Here, we discuss the diversity of glycemic status associated with metabolic surgery and the potential mechanisms of T2D remission. We also highlight the relationship between the change in low-grade inflammation and T2D remission after metabolic surgery. We hypothesize that the level of inflammatory and anti-inflammatory cytokines controls the efficacy of metabolic surgery in patients with T2D. This hypothesis may provide further insight into the mechanism of the beneficial effects of metabolic surgery patients with T2D.
Keywords: Metabolic surgery; Type 2 Diabetes; Glycemic status; Low-grade inflammation